Civics Learning Strategies in Elementary Madrasahs: Theory, Implementation, and Relevance in Building Student Character - Isra Isra; Lisnawati Lisnawati; Muhammad Shaleh Assingkily (Journal of Contemporary Islamic Primary Education, 2026)
Civic Education learning strategies at the Madrasah Ibtidaiyah/Elementary School level play a crucial role in shaping the character, moral values, and civic awareness of students from an early age. The reality in the field shows that civic education is still often delivered in a conventional, teacher-centered manner, which is less able to foster active engagement and value internalization among students. This paper aims to examine in depth various PKn learning strategies that are appropriate for MI/SD, including inquiry-based, cooperative, problem-based learning, character habituation, and technology-based strategies. The method used is library research with a descriptive qualitative approach. The results of the study show that the application of varied, contextual, and student-centered learning strategies has proven effective in improving students' understanding, attitudes, and civic skills. Supporting factors for the success of these strategies include teachers' pedagogical competence, school infrastructure readiness, as well as family and social environment involvement. Meanwhile, inhibiting factors include the limited digital competency of teachers, a lack of innovative teaching material references, and low active student participation due to monotonous teaching methods. The implications of this paper emphasize the importance of continuous professional development for PKn teachers at MI/SD so that they can apply innovative, adaptive, and relevant learning strategies in line with current developments.